Spatial Bioeconomic Analysis of Grouper Fishing on the Fisheries Management Framework in Saleh Bay : Analisis Bioekonomi Spasial Perikanan Kerapu Dalam Kerangka Pengelolaan Perikanan Di Teluk Saleh - Diding Sudira Efendi; Luky Adrianto; Yonvitner; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
This study aims to determine the performance of small-scale grouper fisheries in Saleh Bay using a spatial bioeconomic approach. The optimal fishing trip allocation and economic rent based on the fishing grounds and its season were estimated using this approach. The results showed from the seven main fishing grounds (DPI) in Saleh Bay, the highest optimal trip need to be allocated to DPI-7 with approximately 2833 trips per year, followed by DPI-5 (2107), DPI-1 (1158), DPI -4 (1064), DPI-6 (970), DPI-2 (940) and DPI-3 (524). The intensity of fishing trip responded to the quasi-profit. The grouper catches produced quasi-profits of IDR 1.4 billion per year. The maximum and minimum annual profits of IDR 428 million and IDR 55 million were achieved in DPI-7 and DPI-3, respectively. This trip allocation complements the existing restriction management instrument, related to the control of input, area and season closure options. This strategy choice eases the fisheries managers to focus on spatial and temporal control efforts with high resolution.